Investigating the Influence of Protic Ionic Liquid on the Triboelectrical Properties of Trimethylolpropane Trioleate (TMPO) - Nur Aisya Affrina, Mohamed Ariffin; Yeoh, Sze Yun; Siti Hartini, Hamdan; Lee, Chiew Tin (Penerbit UTM Press, 2024)
Under triboelectric conditions, where tribocharging accelerates lubrication failure, lubricants with enhanced electrical properties are essential. Trimethylolpropane Trioleate (TMPO) oil, derived from esters that possess good lubricating properties and wear performance but is lacking in terms of electrical properties which can be further improved when blended with Ionic Liquid. This study blends 1 – 5 wt% of Protic Ionic Liquid (PIL) into TMPO and evaluate the frictional and wear performances of the blends under 1 – 2 A current conditions to understand the behaviour towards the tribological properties of different blends of material. Electric currents ranging around 1 – 2 A are implemented to the custom-designed ball-on-disc tribometer, with a constant 4.5 V voltage supply and the static resistance are measured. Mechanical wear properties are observed after the tribological test with different samples. The frictional properties of all concentrations of PIL in TMPO showed significant frictional improvements with 1%wt PIL showed 53% better results indicating improvements in frictional properties and wear performance under 2A current conditions, owing to its lowest film resistivity of 0.14 mΩ.